Springs оf Stavropol аs а Reserve Water Supply Facility аnd Ecological Monitoring оf Springs оf Stavropol - I. V. Begdai; E. V. Bondar; E. V. Harina; Y. V. Yeremeeva; M. V. Gasuykova (Наука. Инновации. Технологии, 2023)
Introduction. This paper presents the results of monitoring the natural spring waters of Stavropol. The complex analysis includes hydrochemical and microbiological analyses. The research of spring water samples was carried out in a period from autumn to spring, 2021–2022, a total of 45 samples from five springs in Stavropol were analyzed – Koryta, Chasha, Mikhaylovskiy, Kholodnyy and Serafima Sarovskogo.Materials and research methods. Sampling was carried out in accordance with GOST 31861-2012. Water. General requirements for sampling. Hydrochemical and microbiological analysis was carried out in accordance with SanPiN 2.1.4.1175-02. Hygienic requirements for the quality of water of non-centralized water supply. Sanitary protection of sources.Research results and their discussion. According to the results of hydrochemical analysis of water quality, contamination of Cd, Pb, Ni, Fe was detected during all periods of the study. There was also an excess of the norm in terms of chlorides in all springs in spring, 2022. It was determined that the WPI and quantitative estimation of microorganisms vary significantly both by sampling dates and by springs. The highest rate of WPI was noted for the Mikhaylovskiy spring in the spring of 2022, and quantitative estimation of microorganisms does not exceed acceptable limits.Conclusions. As a result of the conducted research, it can be concluded that the use of spring water in Stavropol in case of an emergency without risks to public health is possible only from springs – Koryta, Chasha and Kholodnyy, but with preliminary additional cleaning and for a short time.